Alternate spaces and times to the organization of school life: Análisis de las acciones y los sentidos que los niños y las niñas le dan a diferentes momentos y lugares de la escuela. Una revisión de la literatura - Patiño Hurtado, Carolina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This article aims to present an analysis of the actions and meanings that children give to the spaces and times that transcend the regulation of the organization of school life, as an escape from the rules that constitute it. The above, in an attempt to make visible other ways of inhabiting the school, and to recognize self-managed skills by children. Thus, an approach to the state of the art will be approached from categories such as: school spaces, school times and school experiences, with research located from 2002 to 2021.